1998
DOI: 10.1183/09031936.98.11040801
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoproteinaemia: a new perspective in the assessment of lung disorders

Abstract: The glomerular and alveolar capillary walls share several features in their structure and function. Both consist of endothelial and epithelial layers resting on their respective basal membrane. A basic common requirement for an appropriate functioning of these barriers is that they should allow a free diffusion and/or filtration of small molecules (solutes and gases) but efficiently retain larger plasma proteins. The functional capacity of these barriers mainly depends on their available exchange/filtration su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…The lack of correlation between CC16 in serum and albumin in BALF is not inconsistent with that hypothesis, since these proteins show substantial differences with respect not only to their sizes, but also their directions, routes and mechanisms of passage across the air-blood barrier. Although little is known about their exact routes and sites of passage, proteins moving across the air-blood barrier have to be transferred across the epithelial and the endothelial layers, their respective basal membranes, as well as the interstitium [11,12,32]. Several lines of evidence suggest that proteins cross the air-blood barrier paracellularly, through water-filled pores located at the junctional complexes linking epithelial and endothelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correlation between CC16 in serum and albumin in BALF is not inconsistent with that hypothesis, since these proteins show substantial differences with respect not only to their sizes, but also their directions, routes and mechanisms of passage across the air-blood barrier. Although little is known about their exact routes and sites of passage, proteins moving across the air-blood barrier have to be transferred across the epithelial and the endothelial layers, their respective basal membranes, as well as the interstitium [11,12,32]. Several lines of evidence suggest that proteins cross the air-blood barrier paracellularly, through water-filled pores located at the junctional complexes linking epithelial and endothelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent human and experimental studies, the integrity of the air-blood barrier and its permeability to macromolecules might be assessed less invasively by the quantification, in serum, of lung-specific secretory proteins, also referred to as "pneumoproteins" [11,12]. One of these proteins is the Clara cell secretory protein, a low-molecular-weight protein of 16 kDa (CC16), secreted in large amounts into the lumen of the respiratory tract by nonciliated bronchiolar Clara cells [13,14].…”
mentioning
confidence: 99%
“…1 In fact, the serum levels of the pneumoproteins SP-A, SP-B, and CC16 reflect the permeability and/or cellular integrity of the pulmonary epithelium. [38][39][40] Bernard et al 1 found that the regular attendance of an indoor chlorinated pool was the main factor affecting lung epithelium of children, with a positive dose-effect relationship between cumulated pool attendance and serum SP-A and SP-B levels. CC16 was also positively associated with cumulated pool attendance, but no clear dose-effect relationship emerged.…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Nonasthmmentioning
confidence: 99%
“…A study among Belgian schoolchildren claimed that visiting chlorinated pools was strongly related to the prevalence of asthma and positive exercise-induced bronchoconstriction [7]. Furthermore, a positive dose-effect relationship was found between pool attendance in adults and children and serum surfactant protein-A and -B, which are markers of lung epithelium hyperpermeability in a variety of acute or chronic lung disorders [8,9]. However, as swimming is often considered healthy for asthmatics, especially for children, asthma-related referral to improve their general condition might play a role in exacerbating their symptoms and the meaning of changes in biomarker levels is unclear [6].…”
mentioning
confidence: 99%